Post‐traumatic stress symptoms in Swedish obstetricians and midwives after severe obstetric events: a cross‐sectional retrospective survey. (26th August 2016) - Wahlberg, Å; Andreen Sachs, M; Johannesson, K; Hallberg, G; Jonsson, M; Skoog Svanberg, A; Högberg, U
Abstract : Objective: To examine post‐traumatic stress reactions among obstetricians and midwives, experiences of support and professional consequences after severe events in the labour ward. Design: Cross‐sectional online survey from January 7 to March 10, 2014. Population: Members of the Swedish Society of Obstetrics and Gynaecology and the Swedish Association of Midwives. Methods: Potentially traumatic events were defined as: the child died or was severely injured during delivery; maternal near‐miss; maternal mortality; and other events such as violence or threat. The validated Screen Questionnaire Posttraumatic Stress Disorder (SQ‐PTSD), based on DSM‐IV (1994) 4th edition, was used to assess partial post‐traumatic stress disorder (PTSD) and probable PTSD. Main outcome measures: Partial or probable PTSD. Results: The response rate was 47% for obstetricians ( n = 706) and 40% ( n = 1459) for midwives. Eighty‐four percent of the obstetricians and 71% of the midwives reported experiencing at least one severe event on the delivery ward. Fifteen percent of both professions reported symptoms indicative of partial PTSD, whereas 7% of the obstetricians and 5% of the midwives indicated symptoms fulfilling PTSD criteria. Having experienced emotions of guilt or perceived insufficient support from friends predicted a higher risk of suffering from partial or probable PTSD. Obstetricians and midwives with partial PTSD symptoms chose to change their work to outpatient care significantly more often than colleagues without these symptoms. Conclusions: A substantial proportion of obstetricians and midwives reported symptoms of partial or probable PTSD after severe traumatic events experienced on the labour ward. Support and resilience training could avoid suffering and consequences for professional carers. Tweetable abstract: In a survey 15% of Swedish obstetricians and midwives reported PTSD symptoms after their worst obstetric event Tweetable abstract: In a survey 15% of Swedish obstetricians and midwives reported PTSD symptoms after their worst obstetric event